847 GFR measurement and nephrotoxic chemotherapy dose reduction in paediatric sarcoma patients, a three centre study. (17th August 2022) - Lumb, Blanche; Brown, Mia; Capsomidis, Anna; Shamma, Menna; Mycroft, Julie; Rees, Helen; Adams, Madeleine
Abstract : Aims: Ifosfamide and methotrexate are commonly used in the treatment of paediatric sarcoma patients and require careful monitoring of renal function and estimation of glomerular filtration rate (GFR) due to nephrotoxic side effects. Using radiolabelled isotopes to measure GFR is common in paediatric patients due to increased accuracy, reliability and the difficulties of urine collection. However, it is an invasive and expensive test with unavoidable radiation exposure. With no current national guideline on GFR monitoring there is significant variation in practice. This study aims to evaluate frequency of GFR monitoring, across three paediatric oncology centres, and the impact it had on chemotherapy dosing. Recommendations will be made to standardise practice, identify risk factors for renal toxicity and consider frequency of radioisotope GFR measurement Methods: A retrospective analysis of all paediatric patients diagnosed with Ewing's sarcoma, osteosarcoma or rhabdomyosarcoma, requiring ifosfamide or methotrexate chemotherapy, from January 2019 – January 2020 was conducted. Data collected included; age, diagnosis, baseline renal function, underlying renal conditions, renal function monitoring during treatment (via isotopic GFR or other method) and any chemotherapy dose reduction. Data has also been included from a previous audit of GFR use from the Royal Marsden Hospital collected in 2013. Data was collated from patients' clinical notes and online test portals local to each site Results: 85 patients were eligible for inclusion with 17 patients excluded for incomplete data. The age ranged from 1 month to 21 years, with an average age of 9 years. 62 patients had formal isotope clearance GFR testing and 6 patients had GFR testing via other methods. The 62 patients who received isotope measurement of GFR had a total of 244 GFR tests with an average of 3.9 GFRs per patient (range 1 – 10). Four patients required dose reductions, 2 for bone marrow suppression, 1 for tubulopathy (no change in GFR) and 1 patient for reduction in GFR with no change in baseline creatinine (serum creatinine 41, baseline 60). Two patients had ifosfamide substituted by cyclophosphamide, 1 for acute kidney injury post nephrotoxic antibiotic and 1 for hydronephrosis secondary to mass effect from the primary tumour. 5 patients had delayed methotrexate clearance (>72 hours) but did not have an abnormal GFR. Out of 244 GFRs completed only 1 result led to a change in treatment. Conclusion: This study demonstrated that despite wide variation in practice between treatment centres there was a very low rate of chemotherapy dose reduction due to abnormal GFR results in the paediatric population. The results suggest fewer formal GFR tests could be performed without compromising patient safety. Instead GFR testing may be best used in the context of risk factors such as known renal disease, a rise in baseline creatinine or concurrent use of nephrotoxic drugs or to complement other less hazardous monitoring tests, such as serial creatinine or creatinine clearance. This would reduce the radiation burden and cost significantly. Data from this study could be used to inform a new guideline for renal monitoring in sarcoma patients which will be discussed at the conference.